Activation of Receptors δ (PPARδ) by Agonist (GW0742) may Enhance Lipid Metabolism in Heart both In Vivo and In Vitro - Kuo, S.-C.; Ku, P.-M.; Chen, L.-J.; Niu, H.-S.; Cheng, J.-T. (Hormone and Metabolic Research, 2013)
It has been documented that cardiac agents may regulate the lipid metabolism through increased expression of PPARδ in cardiac cells. However, the effect on lipid metabolism by direct activation of PPARδ is still unknown. The present study applied specific PPARδ agonist (GW0742) to investigate this point in the heart of Wistar rats and in the primary cultured cardiomyocytes from neonatal rat. Expressions of PPARδ in the heart and cardiomyocytes after treatment with GW0742 were detected using Western blots. The fatty acid (FA) oxidation and the citric acid (TCA) cycle related genes in cardiomyocytes were also examined. In addition, PPARδ antagonist (GSK0660) and siRNA-PPARδ were employed to characterize the potential mechanisms. After a 7-day treatment with GW0742, expressions of PPARδ in the heart were markedly increased. Increased expressions of FA oxidation and TCA cycle related genes were also observed both in vivo and in vitro. This action of GW0742 was blocked by GSK0660 or by siRNA-PPARδ. The obtained results show that activation of PPARδ by GW0742 is responsible for the increase of FA oxidation and TCA cycle related genes in hearts. Role of PPARδ in the regulation of lipid metabolism in heart is then established.
Keywords: cardiomyocytes; digoxin; fatty acid oxidation; TCA cycle gene; PPARδ